2010
DOI: 10.1002/bem.20564
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency magnetic field effects on molecular dynamics and iron uptake in cage proteins

Abstract: The protein ferritin has a natural ferrihydrite nanoparticle that is superparamagnetic at room temperature. For native horse spleen ferritin, we measure the low field magnetic susceptibility of the nanoparticle as 2.2 x 10(-6) m(3) kg(-1) and its Néel relaxation time at about 10(-10) s. Superparamagnetic nanoparticles increase their internal energy when exposed to radio frequency magnetic fields due to the lag between magnetization and applied field. The energy is dissipated to the surrounding peptidic cage, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Ferritin is the main cellular iron storage protein (Arosio et al, 2017), and it has been reported that RF waves disturb its capacity to handle iron (Cé spedes and Ueno, 2009;Cé spedes et al, 2010). Next, we tested the effects of RF exposure on the LIP in cells loaded with calcein (Figure 1E).…”
Section: Rf Stimulation Increases the Labile Iron Pool (Lip)mentioning
confidence: 99%
“…Ferritin is the main cellular iron storage protein (Arosio et al, 2017), and it has been reported that RF waves disturb its capacity to handle iron (Cé spedes and Ueno, 2009;Cé spedes et al, 2010). Next, we tested the effects of RF exposure on the LIP in cells loaded with calcein (Figure 1E).…”
Section: Rf Stimulation Increases the Labile Iron Pool (Lip)mentioning
confidence: 99%
“…We studied the effects of RF electromagnetic fields on iron ion release and uptake from and into the ferritins. As shown in Figure 9, we observed that the amount of iron chelated after 1 h is reduced by up to a factor of 3 in proteins previously exposed to RF electromagnetic fields of 1 MHz and 30 μT for 5 h (Céspedes & Ueno, 2009; Cespedes et al., 2010). The error bars in Figure 9 are calculated as the standard error of the mean.…”
Section: Effects Of Radio Frequency Electromagnetic Fields On Iron Release and Uptake From And Into Iron Cage Proteins Ferritinsmentioning
confidence: 71%
“…The significant inhibition of RF-AMF driven SEAP production by GSK, with and without capsaicin, suggests that NOX1/2-generated ROS in HEK-293T cells, plays a role in TRPV1 activation, and this ROS is potentiated in the presence of capsaicin. However, even in the absence of capsaicin, ROS may be formed from ferritin upon RF-AMF treatment without a potentiator 33 (Hernandez-Morales et al, 2020), likely due to AMF effecting local iron levels around ferritin 40,41 (Céspedes et al, 2009, 2010). To understand better the role of ROS under RF-AMF conditions, HEK-293T cells stably expressing the αGFPnb-V1/GFP-FtD magnetogenetics construct were exposed to RF-AMF and both intra- and extracellular ROS levels were measured using DCFDA and Amplex Red, respectively.…”
Section: Resultsmentioning
confidence: 99%